Juridical Review of the Legalization of the Deed of Establishment of a Limited Liability Company on-Line through the Sisminbakum - Emmy Butarbutar (Institute Of computer Science (IOCS), 2022)
Limited Liability Company (PT) is a form of legal entity in Indonesia. A company obtains the status of a legal entity after the deed of establishment is approved by the Minister of Law and Human Rights. To obtain the legalization of a legal entity, a notary as the power of attorney submits an application for legalization of the establishment of a PT through information technology services for the Legal Entity Administration System (Sisminbakum) electronically to the Minister of Law and Human Rights by filling out the Model I Form. The online legal entity legalization service through Sisminbakum is an issue new in Law no. 40 of 2007 concerning Limited Liability Companies, but in reality the Sisminbakum has been in effect since 2001, while UUPT No 1 of 1995 does not regulate the process of ratifying the deed of establishment of a PT whether it is done manually or electronically. The problem in this thesis is regarding the procedure for establishing a PT based on UUPT No 40 of 2007, the legal basis for the ratification of the deed of establishment of a PT online through Sisminbakum, the procedure for ratifying the deed of establishment of a PT online and the legal certainty of the SK legalization of the legal entity PT which is signed electronically. Sisminbakum is an official website which is a computerized system in ratifying the establishment of a legal entity owned by the Directorate General of General Legal Administration (Dirjen AHU). The application for legalization of the company's deed of establishment is submitted by a notary through the Sisminbakum by filling out the Model I Form I (FIAN I). The steps that must be taken in the FIAN I application through this Sisminbakum are: checking the name, then filling out the Pre FIAN I Supporting Documents (FIAN I Prerequisites) then filling in the data in the FIAN I process then correcting and ending the sending of Physical Documents. If the physical documents are complete and meet the requirements, the Decree will be signed electronically by the Minister of Law and Human Rights and then sent to the notary who requests it. The decision letter for ratification of this PT has strong legal force